Esquisser un avenir sans drogue en détention préventive (Genève, 1970-1980) - Mirjana Farkas; Cristina Ferreira (Criminocorpus)
Arrested and remanded in custody during the 1970s and 1980s, young drug addicts have left behind poignant writings. Preserved in the archives of the Institute of Legal Medicine in Geneva, these documents were produced at a time when drugs were becoming a major public problem. In prison, doctors, psychiatrists, psychologists and chaplains were providing various forms of assistance, which have not been well documented to date. The practice of introspective writing, which they encouraged among drug-addicted prisoners, was one of the means of understanding, knowing and acting. Over the years, a body of knowledge has been built up, paving the way for a public policy of prevention.